(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper the concept of safe limit in the framework for continuously moving objects to monitor result changes of spatio temporal queries has been proposed. In this framework the movement of the moving object is monitored with the help of user defined aggregate function over spatio temporal reference in data stream management system. The expected movement of the moving object is plotted on the graph and the spatio temporal queries are answered on the basis of that, until and unless the difference between the expected movement and actual movement is more than the safe limit. This makes the framework more efficient than the previously given framework. The safe limit can be any range with respect to space and time of a moving object which varies according to different parameters such as size of the object, velocity with which it is moving and etc.